How is knowledge shared in Public involvement? A qualitative study of involvement in a health technology assessment - Emma J. Cockcroft; Nicky Britten; Linda Long; Kristin Liabo (Wiley, 2020)
Abstract Background Public involvement in research is seen as a quality marker by funders. To understand the process and impact of involvement, more in‐depth studies are needed on how members of the public contribute in meetings with researchers. Objectives This study aimed to observe and reflect on what is said by public advisers in involvement. We wanted to understand (a) what knowledge and experience is shared during research meetings, and (b) how this knowledge is shared with researchers. Methods Data were collected in November 2016 as part of the public involvement in a health technology assessment of lung cancer screening using low‐dose computed tomography. Three meetings were audio recorded and observed with the purpose of understanding how members of the public contributed during the meetings. Audio recordings were transcribed verbatim and data analysed using a thematic approach, with the coding framework developed inductively. We also included reflections from a community drop‐in session. Results Members of the public brought three different 'sources' of knowledge and experience to meetings with researchers: direct lived personal experience; learnt knowledge; and the experience and values of others. The data suggest that group settings allow for dynamic discussions and sharing of different types of knowledge. Conclusion Group‐based involvement meetings allow for the synergistic combination of individual knowledge and experience. This gives researchers a broader understanding of the topic, which can be the vehicle for patient impact on the research. A combination of group meeting and community drop‐in can enable more varied input into research planning and conduct.